Association Between Estrogen Receptors and GATA3 in Bladder Cancer: A Systematic Review and Meta-Analysis of Their Clinicopathological Significance - Bernardo, Carina; Monteiro, Fátima L.; Direito, Inês; Amado, Francisco; Afreixo, Vera; Santos, Lúcio L.; Helguero, Luisa A. (Frontiers in Endocrinology, 2021)
Background: Estrogen receptors alpha (ERα) and beta (ERβ), and GATA-binding factor 3 (GATA3) have been implicated in bladder carcinogenesis and tumour progression. They have been functionally linked in luminal fate of breast cells, but to date their relationship in bladder cancer has not been established. This information will be useful to advance diagnostic and prognostic markers. Aim: Determine the relationship between the expression of ERα, ERβ and GATA3 in bladder cancer, disclose their prognostic and diagnostic value and their association with clinicopathological characteristics. Methods: A comprehensive literature search in PubMed database was performed for all immunohistochemical studies of ERα, ERβ and/or GATA3 in bladder cancer patients. We selected eligible studies in accordance with the PRISMA guidelines and evaluated methodological quality and risk of bias based on quality criteria from the reporting recommendations for tumour MARKer (REMARK) prognostic studies. Risk of bias assessment was performed using Review Manager 5. R software was used for all statistical analysis, the packages used were meta and dmetar for the standard meta-analysis, and netmeta for the network meta-analysis. Results: Thirteen studies were eligible for ERα, 5 for ERβ and 58 for GATA3 meta-analysis. Low grade tumours showed significantly lower ERα expression. GATA3 was widely expressed in bladder tumours, especially urothelial carcinomas, with higher expression of GATA3 in low grade and low stage tumours. Data was insufficient to determine the prognostic value of either ERα or ERβ, but GATA3-positivity was associated with higher recurrence free survival. A negative correlation between ERα or ERβ positivity and GATA3 expression was disclosed. Additionally, several sources of heterogeneity were identified, which can be used to improve future studies. Conclusion: The clinicopathological value of ERα and ERβ was inconclusive due to low availability of studies. GATA3 emerged as good prognostic marker; while ERα-positivity was associated to higher grade tumours. ERα and ERβ were inversely correlated with GATA3 expression. Considering that bladder cancer cell lines were shown to have functional ERs, a comprehensive analysis of ERα and ERβ expression in BlaCa supported by complete patient clinical history is required for the identification of patients that may benefit from treatment with hormonal therapy.